2023
DOI: 10.2196/47152
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Informal Caregivers of People With Dementia in Web-Based Psychoeducation Programs: Systematic Review and Metasynthesis

Abstract: Background Informal caregivers of people living with dementia experience a higher level of physical and mental stress compared with other types of caregivers. Psychoeducation programs are viewed as beneficial for building caregivers’ knowledge and skills and for decreasing caregiver stress. Objective This review aimed to synthesize the experiences and perceptions of informal caregivers of people with dementia when participating in web-based psychoeducat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 63 publications
(204 reference statements)
0
2
0
Order By: Relevance
“…On the one hand, active psychoeducation programs refer to a therapeutic setting with guidance and specific interventions, such as those found in group therapy [ 27 ]. Numerous studies suggest that active psychoeducation programs are effective in treating a variety of mental disorders, including anxiety disorders, depression, or chronic pain disorders, but can also reduce caregivers’ burden (for a meta-analysis, see [ 27 , 28 , 29 , 30 , 31 ]). In addition, previous research has shown that active psychoeducational stress management training is also a successful intervention for university students to reduce stress, depression, and other psychological symptoms, although the effect size is rather small (e.g., meta-analyses and reviews by [ 32 , 33 ]).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, active psychoeducation programs refer to a therapeutic setting with guidance and specific interventions, such as those found in group therapy [ 27 ]. Numerous studies suggest that active psychoeducation programs are effective in treating a variety of mental disorders, including anxiety disorders, depression, or chronic pain disorders, but can also reduce caregivers’ burden (for a meta-analysis, see [ 27 , 28 , 29 , 30 , 31 ]). In addition, previous research has shown that active psychoeducational stress management training is also a successful intervention for university students to reduce stress, depression, and other psychological symptoms, although the effect size is rather small (e.g., meta-analyses and reviews by [ 32 , 33 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Psychosocial care includes a spectrum of services and therapies, spanning from educational interventions that systematically provide information to intensive one-on-one counseling sessions [ 14 ]. Psychosocial intervention has emerged as a therapeutic strategy designed to address the multifaceted challenges faced by ALS/MND patients and their caregivers [ 15 17 ]. Over the years, several psychosocial interventions have been developed and implemented to assist ALS/MND patients and their families to cope with the challenges posed by the disease [ 9 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%